ESTETIKA DAN KRITIK SOSIAL DALAM KARYA LIPUTAN “HEGEMONI INDUSTRI KOPI” DI CHANNEL YOUTUBE SUAR NUSANTARA - Cory Amelia Lorenza (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2021)
The rise of coffee shops in the city of Bandung has made the coffee industry sector grow rapidly. This industry generates a lot of profits from upstream “farmers” to downstream “entrepreneurs” of coffee shops. However, at the same time, this industry creates quite a big problem, especially in the presentation media and the waste generated from the industry. Suar Nusantara managed to package it in a work of coverage that combines elements of art in it. This study uses a qualitative method with semiotic analysis of Roland Barthes. From the results of the research, it is known that the work covering the "Hegemony of the Coffee Industry" denotatively describes the culture of drinking coffee which has become a lifestyle. In addition to the denotative meaning of coffee culture, connotative meanings were also found in the use of performance art elements as a form of criticism of the consumption of waste from the coffee industry which is described as accumulating and adding new traces of waste accumulation from the emergence of various coffee shops and lifestyles in the era of modernization. There are also tactics in delivering the message, namely by packaging it in a pop way to attract the attention of the millennial audience.